A comparison of the effects of different degrees of zona pellucida damage followed by cryopreservation on the postthaw development of mouse embryos - Lee, Robert Kuo-Kuang (Springer-Verlag, 1997)
Purpose:The totally intact zona pellucida is not essential for the development of embryos. It is still unclear how much effect the degree of damages to the zona pellucida will have on the developmental potential of postthaw embryos after cryopreservation. We compared the developmental potential of cryopreserved mouse embryos after induction of two degrees of mechanical damage to the zonae pellucidae by micromanipulation. Methods:In experiment I, the development of 124 cryopreserved ICR mouse embryos to the blastocyst stage after zona pellucida penetration of two-cell embryos as in the procedures of subzonal sperm insertion (SUZI) was compared with the development of zona-intact cryopreserved embryos. In experiment II, the zonae pellucidae of 93 two-cell mouse embryos were dissected as in the procedures of partial zonal dissection (PZD), following which the embryos were frozen. This postthaw development was also compared with that of zona-intact two-cell cryopreserved embryos. All the embryos were thawed and cultured to the blastocyst stage. Additional controls were provided by culturing zonaintact and zona-penetrated or zona-dissected embryos without cryopreservation. Results:The development of unfrozen mouse embryos was not affected by either zona penetration (P=0.433) or zona dissection (P=0.659). The developmental potential of cryopreserved mouse embryos was significantly affected after zona dissection (blastocyst rate, 31% ZD vs 72%, control; P<0.001) but not after zona penetration (blastocyst rate, 59% ZP vs 64% control; P=0.441). Conclusions:The quality of cryopreserved embryos was affected by a large hole on the zona pellucida created by zona dissection but not by simple zona penetration.